Evaluasi Usability dan Redesign Aplikasi PI-Mobile ITTP Menggunakan Pendekatan UCD (User Centered Design) - Ahmad Fauzan Nabawi; Pradana Ananda Raharja (STMIK Budi Darma, 2023)
The PI-Mobile ITTP application is an academic application to make it easier for new ITTP students or old ITTP students to find various kinds of information such as campus profiles, faculties, education administration, campus ethics, student information, campus facilities, and others. According to the results of the questionnaire distributed to ITTP students using the System Usability Scale (SUS), the usability value was 51.10 which was included in the interval >= 51 and <68 in the adjective rating poor category with grade D. So that improvements to the application design need to be made. The method in this study uses User Centered Design (UCD) because the UCD method involves the application users themselves so they can provide input regarding the usability or convenience of using the PI-Mobile ITTP application. The final result of this study is that after redesigning the appearance of the PI-Mobile ITTP application based on input from users obtained from 34 ITTP student respondents, the usability results tested with SUS obtained a usability value of 79.78 which was included in the interval >=74 and < 80.3 is in the adjective rating good category with grade B. Based on the results of the usability test with SUS and using the UCD method, an increase in usability of 28.68 was obtained, the initial value being 51.10 in the adjective rating poor and the grade D category to 79.78 in the adjective good rating and grade B category.